Culture, Socio-economic Status and Religious Coping As Predictors of Happiness: A Review - Ibrahim Lawal, Zainab; Khan, Aqeel; Bin Ramli, Jamaluddin (International Journal of Psychosocial Rehabilitation, 2020)
Happiness’s importance cannot be overemphasized; this has been confirmed by many researchers and the World Happiness Report 2012–2018. As a result, factors predicting happiness have been employed by researchers and scholars in various studies on Muslim women. Thus, this study examined and found out the factors predicting happiness, such as culture, socio-economic status (SES), and religious coping, as well as identified the foremost and major predictor and research design used by these scholars. A systematic review of the literature on culture, socioeconomic status, and religious coping as predictors of happiness among Muslim women was carried out. A total number of 30 articles from different disciplines have been examined. The factors and research design found were divided into those that belong to happiness predicted by culture, by socio-economic status, by religious coping, and by culture, socio-economic status, and religious coping; happiness related to culture; happiness related to culture, socio-economic status, and religious coping; and happiness related to culture, socio-economic status, and religious coping. The research designs were quantitative, qualitative, mixed method, and systematic literature review (SLR). Quantitative research design was found to be the leading research design. The studies were also examined based on countries of study: Iran, Turkey, Palestine, Oman, Qatar, New Zealand, England, Bangladesh, Algeria, Jordan, Indonesia, Malaysia, and Lebanon. Iran was the leading country. But no model of happiness was found in the studies analyzed. It is hoped that findings from this study will be beneficial to Muslims in women’s centers for continuing education and counselors, especially in sub-Saharan Africa (Nigeria).